Benefits of membrane electrodes in the electrochemistry of metalloproteins: mediated catalysis of Paracoccus pantotrophus cytochrome c peroxidase by horse cytochrome c: a case study - Sousa, P. M. Paes de (2008)
J Biol Inorg Chem. 2008 Jun;13(5):779-87. doi: 10.1007/s00775-008-0365-8